Autonomic dysfunctions in patients with scorpion sting: early predictors of severe disease - Gadari, Kumaraswamy R. C.; Mathada, Sudha Madhavi Kalli (International Journal of Advances in Medicine, 2017)
Background: Scorpion sting envenomation is a common medical emergency accounting for nearly 2.8% of annual intensive cardiac care unit admissions and much more outpatient visits. Symptomatology and severity of envenomation varies greatly. Autonomic storm may end up in loss of life. Methods: This is a clinical study conducted between April 2011 and February 2013. Patients with moderate to severe envenomation were examined at frequent intervals for various autonomic manifestations. Various demographic, clinical and electrocardiogram (ECG) changes were studied for their association with severity of envenomation. Results were statistically evaluated for their significance. Results: A total of 106 patients were studied with a mean age of 27.25 years and peak incidence between 11 and 30 year age groups. 91% reached the hospital within 12 h. 7.55% of the patients had Grade 2, 74.53% had Grade 3 and 17.92% had Grade 4 disease, all grades were common in 11-30 age group. Autonomic disturbances; profuse sweating seen in 72.6% of the patients that showed a strong correlation with pulmonary edema and ECG manifestations (p ≤ 0.0001). Pulmonary edema was present in 37.7% of the patients. Excessive salivation was seen in 28.3%, and persistent nausea and vomiting were seen in 24.5%, both were associated with severe cardio-pulmonary manifestations. Hypotension was present in 14.2% of patients that was associated with poor prognosis (p ≤ 0.0001). Conclusions: Scorpion sting envenomation is a life-threatening problem requiring immediate attention. Presence of autonomic dysfunctions; profuse sweating, excessive salivation, persistent nausea and vomiting, hypotension at presentation are poor prognostic factors.